“I Do Not Feel Confident and Uncomfortable Discussing Patients’ Sexuality Concerns”: A Thematic Analysis of Indonesian Nurses’ Experiences in Discussing Sexuality with Patients - Hayuni Rahmah; Yati Afiyanti; Imami Nur Rachmawati; Titin Ungsianik; Tri Budiati; Wiwit Kurniawati (Jurnal Keperawatan Indonesia, 2020)
Despite the increasing complexity of the tasks and responsibilities in providing nursing care to patients, many Indonesian nurses may not possess adequate knowledge and skills to discuss sexuality with their patients. The purpose of this study is to explore the experience of Indonesian nurses in providing nursing care to patients regarding sexual problems. This research adopted a descriptive qualitative design to explore the experiences of Indonesian nurses in solving their patient’s sexual problems. Ten nurses working in a general hospital in Indonesia participated in this work. These nurses were interviewed extensively, and the data were transcribed and analyzed thematically. Four main themes were identified in this study: (1) Nurses believe that discussing a patient's sexual problems as part of their professional responsibility, (2) discomfort and embarrassments are barriers to providing adequate solutions to help resolve a patient's sexual problems, (3) nurses assume that most patients are not interested in discussing sexual problems because of illness, and (4) nurses do not have the confidence to discuss the patient's sexual problems. The findings of this study confirm that many nurses feel hesitant and uncomfortable when addressing patients' sexual problems. Thus, Indonesian nurses require more training related to providing nursing care to patients with sexual problems.  Abstrak “Saya Merasa Tidak Percaya Diri dan Tidak Nyaman dalam Mendiskusikan Masalah Seksual”: Analisis Tematik Pengalaman Perawat Indonesia Mendiskusikan Masalah Seksual Pasien. Terlepas dari meningkatnya kompleksitas tugas dan tanggung jawab dalam memberikan asuhan keperawatan kepada para pasien, banyak perawat Indonesia mungkin tidak memiliki pengetahuan dan keterampilan yang memadai untuk membahas seksualitas dengan pasien mereka. Tujuan dari penelitian ini adalah untuk mengeksplorasi pengalaman perawat Indonesia dalam memberikan asuhan keperawatan kepada pasien terkait masalah seksual. Penelitian ini mengadopsi desain deskriptif kualitatif untuk mengeksplorasi pengalaman perawat Indonesia dalam menyelesaikan masalah seksual pasien mereka. Sepuluh perawat yang bekerja di rumah sakit umum di Indonesia berpartisipasi dalam penelitian ini. Perawat diwawancarai, kemudian data ditranskripsi dan dianalisis secara tematis. Empat tema utama diidentifikasi dalam penelitian ini: (1) Perawat percaya bahwa mendiskusikan masalah seksual pasien adalah bagian dari tanggung jawab profesional mereka, (2) ketidaknyamanan dan rasa malu adalah hambatan untuk memberikan solusi yang memadai untuk membantu menyelesaikan masalah seksual pasien, (3) perawat menganggap bahwa sebagian besar pasien tidak berminat mendiskusikan masalah seksual karena penyakitnya, dan (4) perawat tidak memiliki percaya diri untuk mendiskusikan masalah seksual pasien. Temuan penelitian ini mengkonfirmasi bahwa banyak perawat merasa ragu dan tidak nyaman ketika menangani masalah seksual pasien. Oleh karena itu, perawat Indonesia membutuhkan lebih banyak pelatihan terkait memberikan asuhan keperawatan kepada pasien yang memiliki masalah seksual. Kata Kunci: deskriptif kualitatif, masalah seksual, perawat Indonesia, perawatan seksual